Strategi Perguruan Tinggi Hukum dalam Menghadapi Era Disrupsi Teknologi Sebagai Upaya Membentuk Para Penegak Hukum yang Berintegritas dan Berkarakter Pancasila: Strategy of Law Colleges in Facing the Era of Technological Disruption as an Effort to Create Law Enforcers with Integrity and Pancasila Character - Rosana, Annisa Suci; Dewi, Monika Dita Puspa; Baiquni, Muhammad Iqbal (Fakultas Hukum Universitas Negeri Semarang, 2021)
Law colleges are educational institutions that have a crucial role in shaping human resources who are ready to become law enforcers by prioritizing integrity, and being able to adapt to technology. This is in line with the world that is facing an era where there is a massive change taking place very quickly in various sectors which is called the era of disruption. One of the sectors experiencing the impact of the era of disruption is technology. The era of technological disruption certainly brings its own challenges and opportunities for various elements, one of which is law universities. In terms of challenges, in the era of technological disruption, law colleges as educational institutions must be able to prepare their students to be technology literate so that later when they graduate, they can compete in the global world of work. The era of technological disruption besides bringing challenges, of course also brings opportunities if it can be utilized to the maximum extent possible by the university, one of which is by utilizing digital technology with artificial intelligence (AI) to change teaching and learning procedures with innovations that can make it easier for students. This study aims to answer 2 problem formulations, namely: 1). How is the Law College as an educational institution that can produce law graduates with integrity and Pancasila character?, and 2).How is the strategy of law universities in preparing prospective law enforcement officers in the era of technological disruption?. This study uses the Statute Approach and Case Approach in providing an overview of law colleges as educational institutions in facing the era of technological disruption.